The Interpretation of Tropical Architecture in Designing University of Sumatera Utara Student Dormitory - Aida Mayaseva; Morida Siagian (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
University of Sumatera Utara (USU) is a state university in Medan with many enthusiasts who want to study there. The provision of student dormitories and facilities is very important to support the development and development of the younger generation in pursuing higher education. The function of this dormitory is not only as a place to live, but also has a role in supporting non-academic activities such as sports, developing student interests, and talents through coaching programs that aim to shape student personalities. Given that the design location is a tropical climate with a fairly hot air temperature, the design of this student dormitory applies tropical architectural design principles.